The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/npp.2013.310
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Acute Intranasal Oxytocin Produce Divergent Social Effects in Mice

Abstract: Intranasal administration of oxytocin (OXT) might be a promising new adjunctive therapy for mental disorders characterized by social behavioral alterations such as autism and schizophrenia. Despite promising initial studies in humans, it is not yet clear the specificity of the behavioral effects induced by chronic intranasal OXT and if chronic intranasal OXT could have different effects compared with single administration. This is critical for the aforementioned chronic mental disorders that might potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
169
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 59 publications
18
169
5
1
Order By: Relevance
“…While our data implicate OXT as a treatment option for disorders associated with social fear, such as SAD, more detailed studies regarding acute and long-term treatment effects on molecular, neuronal, and behavioral levels are required. This is more evident as chronic central as well as peripheral OXT treatment in mice affected brain OXTR binding (Huang et al, 2013;Peters et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…While our data implicate OXT as a treatment option for disorders associated with social fear, such as SAD, more detailed studies regarding acute and long-term treatment effects on molecular, neuronal, and behavioral levels are required. This is more evident as chronic central as well as peripheral OXT treatment in mice affected brain OXTR binding (Huang et al, 2013;Peters et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These data highlight important timing (acute vs chronic and developing vs mature), dose, and sex effects on social behavior outcomes after exogenous manipulation of oxytocin. A recent study in adult male mice also revealed a counterintuitive reduction in social investigation after chronic intranasal oxytocin (Huang et al, 2014). Combined, these data indicate caution and careful study design for future chronic use of oxytocin in clinical populations.…”
Section: Behavioral Influence During Developmentmentioning
confidence: 92%
“…injection of high OT doses in mice produced higher anxiety-like behavior in a social stress paradigm, which was paralleled by reductions in OTR binding in various brain areas (e.g., amygdala, septum) relevant for stress-regulation (Peters et al, 2014). Similarly, chronic intranasal OT treatment resulted in a reduction of social behaviors and concurrent reductions of OTR binding in the nAcc, amygdala, and anterior olfactory nucleus amongst other brain regions (Huang et al, 2014). Moreover, in a mouse model of ASD, chronic intranasal OT administration did not lead to improvements in social behaviors (Bales et al, 2014).…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%